PARTISIPASI POLITIK PEREMPUAN DI KABUPATEN KEPULAUAN - Fitra Nurmizian; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at the Kabupaten Kepulauan Meranti, exactly at the officeDPRD Kabupaten Kepulauan Meranti . This study aims to determine the things thatencourage and inhibit the participation of women in political parties and legislative aswell as the contribution of party and legislative members as well as their efforts inrealizing gender equality. This study is titled “Partisipasi Politik Perempuan DiKabupaten Kepulauan Meranti”. The main issue of this study is how women canchoose to participate in politics with the various barriers that occur and makecontributions and realize gender equality. Sampling in this research is by purposivesampling. samples is 5 people. The method used is Kualitatif Descriptive method withKualitatif data analysis. The data filtering instruments used are observation, interviewand documentation. The results of this study indicate: women who participated inpolitics were generally first encouraged by their husbands and after getting to know thepolitics deeper there was an incentive in them to do more for the community and alsobecause women's representation in political participation was very small. Barriers thatoccur when they participate in political activities include from culture, environment,and education. As long as they are members of the party and the legislature theyperform their duties well and make efforts such as freedom of expression, persistence inpolitics, political sausageization and forming a special women organization so that theposition of women and men in the same political participation.Key Word: Political participation, Women, Gender Equality